Lithium restores nuclear REST and Mitigates oxidative stress in down syndrome iPSC-Derived neurons - Lam, Xin-Jieh; Maniam, Sandra; Ling, King-Hwa; Cheah, Pike-See (Elsevier Science, 2025)
Down syndrome (DS), caused by trisomy 21, is characterized by intellectual disability and accelerated aging, with chronic oxidative stress contributing to neurological deficits. REST (Repressor Element-1 Silencing Transcription factor) is a crucial regulator of neuronal gene expression implicated in DS neuropathology. This study investigates the neuroprotective potential of lithium, a mood stabilizer with known cognitive-enhancing effects, in restoring levels of REST. Using three pairs of human disomic and trisomic DS induced pluripotent stem cell (iPSC) isogenic lines, we differentiated neurons and treated them with lithium. Nuclear REST expression and reactive oxygen species (ROS) levels were quantified. Results showed the significantly lower nuclear REST expression in DS neurons was restored after 24 hours of 10 mM lithium carbonate treatment. Notably, lithium treatment selectively reduced ROS levels in DS neurons to near-baseline levels. When challenged with hydrogen peroxide, DS neurons exhibited increased vulnerability to oxidative stress. The lithium treatment also significantly reduced ROS levels in the stressed control neurons. These findings reveal a positive association between lithium treatment, REST restoration, and oxidative stress reduction, suggesting that repurposing lithium could contribute to developing therapeutic strategies for DS neuropathologies. This study provides novel insights into DS molecular mechanisms and highlights the potential of lithium as a targeted intervention for improving neuronal functionin DS.